Preparation and chemical and biological characterization of a pectin/chitosan polyelectrolyte complex scaffold for possible bone tissue engineering applications - Coimbra, Patrícia Manuela Almeida (2018)
In this work, porous scaffolds obtained from the freeze-drying of pectin/chitosan polyelectrolyte complexes were prepared and characterized by FTIR, SEM and weight loss studies. Additionally, the cytotoxicity of the prepared scaffolds was evaluated in vitro, using human osteoblast cells. The results obtained showed that cells adhered to scaffolds and proliferated. The study also confirmed that the degradation by-products of pectin/chitosan scaffold are noncytotoxic.